Hubungan Lama Pemakaian Alat Kontrasepsi KB Suntik 3 Bulan Terhadap Kembalinya Kesuburan Pada Akseptor KB di Wilayah Puskesmas Kabupaten Gowa - Sumaifa, Sumaifa; Isnaeny, Isnaeny; J, Halinda; Rahmadanil, Rahmadanil (Universitas Hang Tuah Pekanbaru, 2025)
Family planning is a strategic effort to suppress population growth and improve maternal and child health. One of the contraceptive methods widely used in Indonesia is the 3-month injection. The purpose of this study was to determine the relationship between the duration of use and the return of fertility in 3-month injection contraceptive acceptors. This type of research is a quantitative study using a correlational design with a cross-sectional approach. The study population was 42,644 acceptors of the 3-month injection contraceptive at community health centers in Gowa Regency. Sampling was carried out using purposive sampling according to certain considerations with a sample size of 221 respondents. Data analysis techniques were univariate and bivariate. The results of this study indicate that the duration of use of the 3-month injection contraceptive with the return of fertility, namely with the duration of use of the 3-month injection in the long category, 32 people (14.47%) had a fast return of fertility and 83 people (37.55%) had a slow return of fertility. In the category of recent use of 3-month injectable contraceptives, 47 people (21.26%) and 59 people (26.69%) experienced a slow return to fertility. Based on the results of statistical analysis using the SPSS 21 program using the Chi-square statistical test, the Sig value was obtained = 0.008 < 0.05. It can be concluded that the HO hypothesis is rejected, indicating a relationship between the duration of 3-month injectable contraceptive use and the return of fertility. In conclusion, there is a relationship between the duration of 3-month injectable contraceptive use and the return of fertility.